Performance Assessment of Atmospheric Water Generators: A Review of Evaluation Tools and Proposal for a Novel Advanced Global Evaluation Index for HVAC–AWG Hybrid Solutions - Lucia Cattani; Paolo Cattani; Roberto Figoni; Anna Magrini (Applied Sciences)
In the context of an increasing water crisis and rising energy consumption, an integrated approach to plant design and improvement can be highly effective. Specifically, the use of advanced multipurpose Atmospheric Water Generator (AWG) machines, integrated into existing or new HVAC systems, can improve efficiency while simultaneously extracting atmospheric water. However, hybrid plant configurations, which encompass both integrated and traditional solutions, can be difficult to assess. This paper presents a brief review of the most widely used AWG evaluation tools and proposes a new index, called AGEI, designed to address the knowledge gap in evaluating hybrid plants from an efficiency perspective. The paper shows how this index provides results that more accurately reflect the real efficiency of hybrid plant configurations compared to the Global Evaluation Index (GEI), which is the only existing tool addressed to the evaluation of integrated multipurpose machines. The work is complemented by the application of AGEI to three complex hybrid plant configurations, two of which include a bottling system supplied by desalination for drinking water production. The index is straightforward and requires only knowledge of the useful effects produced by the analysed plant and their corresponding efficiency indicators.